Can the jurist discourse as a social scientist? (Possibilities and impossibilities of law as a social "science") - Haba, Enrique P. (2022)
Knowledge produced in nearly all Social Sciences (Sociology, Political Science,Linguistics, etc.) is almost useless or useless at all —except for scientists themselvesor for their own publishing-market. On the contrary, legal precepts and the doctrineapplied to them bring about a large variety of real effects on the concrete life of allpeople. The price paid for that efficiency is having law built as a web of discourseswithout genuine scientific rigor.